Significance of Indo-Russian Relations for Security Purpose: Exploring Historical Ties and Security Implications (Journal of Advances and Scholarly Researches in Allied Education, 2016)
India-Russia relationship has evolved into an equal partnership. The deep roots of this relationship go back to the early 20th century when India was under British rule and the Czars ruled Russia. The Russian Revolution of 1905 inspired Indian freedom fighters. Mahatma Gandhi was also struck by the similarity in the prevailing conditions in Russia and India. He developed a close connection with Russia and carried on lengthy correspondence with Leo Tolstoy. Russia's communist leader V.I. Lenin followed with interest and sympathy the nascent Indian freedom struggle.